Solving variational problems by homotopy–perturbation method - Abdulaziz, O.; Hashim, Ishak; Chowdhury, Md. Sazzad Hossien (John Wiley & Sons Inc., 2008)
In this paper, we consider some problems in calculus of variations. Homotopy–perturbation method (HPM) is adopted to obtain approximate analytical solutions to variational problems. The solutions are obtained in the form of rapidly convergent infinite series with easily computable terms. Numerical results reveal that HPM is very effective and simple for obtaining approximate solutions to variational problems. Copyright © 2008 John Wiley & Sons, Ltd.